Carta entre José Tous Soto y Roberto H. Todd - Todd, Roberto H.; Tous Soto, José (My University, 1922)
Recomendaciones para vacantes en cargos públicos municipales
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Gay, John; Sheperd, Noah; Rodríguez, Arturo; Martínez, José; Córdova, Jacobo; Vélez, Juan; Santiago, Juan; Rosario, Justiniano; Méndez, Santos; Miranda, Herminio; Lucca, Leonor de